Serum Circ‐FAF1/Circ‐ELP3: A novel potential biomarker for breast cancer diagnosis - Omid‐Shafaat, Ramtin; Moayeri, Hassan; Rahimi, Karim; Menbari, Mohammad‐Nazir; Vahabzadeh, Zakaria; Hakhamaneshi, Mohammad‐Saied; Nouri, Bijan; Ghaderi, Bayazid; Abdi, Mohammad (Journal of clinical laboratory analysis, 2021)
Background Recently, measurement of serum circular RNAs (circRNAs) as a non‐invasive tumor marker has been considered more. We designed the present study to investigate the diagnostic efficiency of serum Circ‐ELP3 and Circ‐FAF1, separately and simultaneously, for diagnosis of patients with breast cancer. Methods Seventy‐eight female patients diagnosed as primary breast cancer participated in this study. We measured the level of circRNAs in serum specimens of the studied subjects. A receiver operating characteristic (ROC) curve was plotted and the diagnostic efficiency for both circRNAs was determined. Results Compared to non‐cancerous controls, Circ‐ELP3 was upregulated in breast cancer patients (p‐value = 0.004). On the other hand, serum Circ‐FAF1 was seen to be decreased in breast cancer patients than controls (p‐value = 0.001). According to ROC curve results, the area under the curve (AUC) for Circ‐ELP3 and Circ‐FAF1 was 0.733 and 0.787, respectively. Furthermore, the calculated sensitivity and specificity for Circ‐ELP3 and Circ‐FAF1 were 65, 64% and 77, 74%, respectively. Merging both circRNAs increased the diagnostic efficiency, with a better AUC, sensitivity and specificity values of 0.891, 96 and 62%, respectively. Conclusion Briefly, our results revealed the high diagnostic value for combined circRNAs panel, including Circ‐ELP3 and Circ‐FAF1 as a non‐invasive marker, in detection of breast carcinomas. Circ‐ELP3 is overexpressed in breast cancer serum specimens. Circ‐FAF1 is decreased in serum sample of patients with breast cancer. Diagnostic efficiency of serum Circ‐FAF1 is higher than Circ‐ELP3 and both of them have the appropriate diagnostic value for breast cancer detection. Combined measurement of Circ‐ELP3 and Circ‐FAF1 has a high diagnostic value and may be considered a diagnostic biomarker for breast cancer detection.